Application and research progress on enhanced external counterpulsation in cardiovascular rehabilitation - Liang Suzhen, Qian Xiaoxian (Xin yixue, 2022)
Enhanced external counterpulsation （EECP） is a non-invasive auxiliary circulatory technology and device, which plays a therapeutic role by synchronizing cardiac systolic and diastolic movement, improving hemodynamics, enhancing vascular endothelial function, and exerting anti-atherosclerosis effect, etc. Currently, EECP is widely applied in the clinical prevention and treatment of cardiovascular diseases, such as chronic heart insufficiency, ischemic cardiomyopathy and refractory angina pectoris. With the gradual attention and continuous promotion of cardiac rehabilitation in China, EECP has played a critical role in the treatment and rehabilitation of cardiovascular diseases. In the future, EECP will serve as an important cardiac adjuvant therapy and benefit patients in primary medical treatment. In this article, the application and research progress on EECP in cardiovascular rehabilitation were reviewed, aiming to provide evidences for the clinical application and development of EECP in cardiovascular rehabilitation.